Impact of outpatient adaptation to home mechanical ventilation on health-related quality of life in patients with COPD: the OutVent study - Carla Ribeiro; Cristina Jácome; Pedro Oliveira; Manuel Luján; Sara Conde (ERJ Open Research)
Background Home mechanical ventilation (HMV) is indicated in patients with severe hypercapnic COPD. Initiation of HMV commonly occurs during an inpatient period, but there has been increasing interest for outpatient adaptation. This study aimed to evaluate the outpatient initiation and adaptation of HMV and its impact on health-related quality of life (HRQoL) in patients with severe COPD. Methods A single-group pre-test–post-test study was conducted in an outpatient ventilation clinic of a tertiary hospital in Portugal. Patients with severe COPD and symptoms of chronic respiratory failure with daytime partial pressure of carbon dioxide (PCO2) ≥50 mmHg in a stable condition or with persistent hypercapnia ≥53 mmHg >14 days following an exacerbation with mechanical ventilation were included. After 3 months of HMV, patients completed the severe respiratory insufficiency (SRI), the S3-noninvasive ventilation (S3-NIV) and a patient experience questionnaire. Results 53 patients (73.6% male, median 71 (p25–p75 61–77) years), with a median forced expiratory volume in 1 s of 35 (29–40)% and a median baseline PCO2 of 53.5 (51.9–56.5) mmHg completed the study. At 3 months patients had a median HMV usage of 6.5 h and decreased their PCO2 by 6.0 mmHg. After 3 months, there was a significant improvement in the SRI summary scale (+5.7), above the minimal clinically import difference of five. Patients who used HMV for more than 5 h had higher S3-NIV total score (6.8 versus 5.7, p=0.04) and S3-NIV sleep and NIV-related side effects subscore (7.1 versus 5.7, p=0.03). Conclusion Our findings might indicate that outpatient initiation and adaptation of HMV has a positive impact in short-term HRQoL in patients with COPD and that this approach is perceived as a positive experience by the patients.